1997
DOI: 10.1063/1.366163
|View full text |Cite
|
Sign up to set email alerts
|

Optically induced rotation of dissymmetrically shaped fluorinated polyimide micro-objects in optical traps

Abstract: Fluorinated polyimide micro-objects (6–7.5 μm cross-sectional radius) fabricated using reactive ion etching have been both optically trapped and simultaneously rotated in both high and low relative–refractive index surrounding media. Symmetrical micro-objects with a low relative–refractive index were optically trapped by exerting optical radiation pressure through their center openings by using a strongly focused trapping laser beam. Micro-objects were both trapped and rotated by the radiation pressure when th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
44
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(44 citation statements)
references
References 37 publications
0
44
0
Order By: Relevance
“…[12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] This work both stimulated and benefitted from more general work on optical rotation and optical torque, most notably from the pioneering work of Les Allen [28][29][30][31][32] and work carried out at The University of Queensland, 7, 10, 33-39 the University of St Andrews [40][41][42][43][44][45][46][47] and the University of Glasgow, [48][49][50][51][52][53][54][55][56][57][58][59] and elsewhere.…”
mentioning
confidence: 99%
“…[12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] This work both stimulated and benefitted from more general work on optical rotation and optical torque, most notably from the pioneering work of Les Allen [28][29][30][31][32] and work carried out at The University of Queensland, 7, 10, 33-39 the University of St Andrews [40][41][42][43][44][45][46][47] and the University of Glasgow, [48][49][50][51][52][53][54][55][56][57][58][59] and elsewhere.…”
mentioning
confidence: 99%
“…Since the pioneering work of Ashkin 1) , the refraction of linear momentum has been widely used to trap and manipulate small particles. Dissymetrically shaped micro-objects have been shown to rotate in optical traps by means of radiation pressure [2][3][4][5][6] . The transfer of photon angular momentum to various types of objects has also been a subject of interest since the early experiments of Beth 7) , who measured the spin angular momentum transferred from circularly polarized light to quartz plates.…”
mentioning
confidence: 99%
“…The force-speed dependence is the function of wave parameters (amplitude E and phase velocity v p ) and film parameters (surface conductivity σ and moving velocity v), implying that ACF can play the role of a transducer from one above mentioned wave or film parameter to another. The physical effects associated with ACF revealed by EM theory and validated by the experiment here have established the working principles for a class of novel sensors and/or actuators with continuously moving part, and may have significance in other quite different science and engineering fields and in wide frequency bands covering RF, microwave and optics [16].…”
Section: Resultsmentioning
confidence: 99%
“…In physics, the scientists have found that electromagnetic (EM) force, referred to radiation pressure in optical frequency band, can manipulate micro-objects [15] and even make micro-objects rotating [16]. The effort has continued so far to enhance radiation pressure [17], but generally it is probably still not big enough for most MEMS applications.…”
Section: Introductionmentioning
confidence: 99%